The Role of Epigenetic Change in Autism Spectrum Disorders - Loke, Yuk Jing; Hannan, Anthony John; Craig, Jeffrey Mark (Frontiers in Neurology, 2015)
Autism spectrum disorders (ASD) are a heterogeneous group of neurodevelopmental disorders characterised by problems with social communication, social interaction and repetitive or restricted behaviours. ASD is comorbid with other disorders including attention deficit hyperactivity disorder, epilepsy, Rett syndrome and Fragile X syndrome. Neither the genetic nor the environmental components have been characterised well enough to aid diagnosis or treatment of non-syndromic ASD. However, genome-wide association studies have amassed evidence suggesting involvement of hundreds of genes and a variety of associated genetic pathways. Recently, investigators have turned to epigenetics, a prime mediator of environmental effects on genomes and phenotype, to characterise changes in ASD that constitute a molecular level on top of DNA sequence. Though in their infancy, such studies have the potential to increase our understanding of the aetiology of ASD and may assist in the development of biomarkers for its prediction, diagnosis, prognosis and eventually in its prevention and intervention. This review focuses on the first few epigenome-wide association studies of ASD and discusses future directions.